Особливості гранулометричного складу ґрунтів під інтродуковані листяними та декоративно-деревними рослинами в парку Тараса Шевченка - Кацевич, Вікторія Валеріївна; Katsevych, Viktoriia; Стрепетова, Христина В’ячеславівна; Strapetova, Khrystyna (My University, 2023)
Дослідження гранулометричного складу ґрунту є ключовим для розуміння його властивостей, таких як здатність утримувати вологу, впливати на ріст рослин та дренажні процеси. Це важливо для визначення водно-повітряного режиму, запобігання ерозії та управління екосистемами. Досліджувався гранулометричний склад ґрунтів під інтродукованими листяно-декоративними деревними рослинами в парку ім. Т. Г. Шевченка. У результаті дослідження було встановлено, що переважна більшість ґрунтів за гранулометричним складом відноситься до суглинку легкого, а вміст фізичної глини коливається в межах від 20,60 до 28,59 %. Серед фракцій у ґрунтах, що досліджувались, переважають піщана (1–0,05 мм), крупнопилувата (0,05–0,01 мм) та мулиста (<0,001 мм). На основі отриманих даних установлені такі типи гранулометричного складу ґрунтів: суглинок легкий піщано-пилуватий, суглинок легкий мулисто-пилуватий, суглинок легкий пилувато-піщаний та суглинок середній мулисто-піщаний. Дослідження підкреслює важливість вивчення гранулометричного складу ґрунтів під інтродукованими деревами для належного управління парковими екосистемами. Гранулометричний аналіз надає цінні дані щодо структури ґрунту, які впливають на його водопроникність, вологовідведення та доступність поживних речовин для рослин. Здатність розуміти та передбачати зміни у гранулометричному складі може бути корисною для забезпечення сталої екологічної стійкості парку та оптимізації умов для росту та розвитку інтродукованих деревних рослин. The study of soil particle size distribution is key to understanding its properties, such as the ability to retain moisture, affect plant growth and drainage processes. This is important for determining the water-air regime, preventing erosion, and managing ecosystems. The research was conducted on the territory of Taras Shevchenko Park, which is located on the right bank of the Dnipro River. The park has about 8 thousand trees and more than 2 thousand shrubs. The composition of the tree and shrub complex is represented by more than 70 species. To determine the granulometric composition of the soils of the park area, soil samples were taken from a depth of 0–20 cm under the crowns of such introduced deciduous and ornamental woody plants as common bitter chestnut (Aesculus hippocastanum L.), sugar maple (Acer saccharum Marshall), low elm (Ulmus pumila L.), western redbud (Celtis occidentalis L.), prickly gleditsia (Gleditsia triacanthos L.), Japanese sophora (Styphnolobium japonicum (L.) Schott), Pennsylvania ash (Fraxinus pennsylvanica Marshall), common robinia (Robinia pseudoacacia L.), red oak (Quercus rubra L.), highest ailanthus (Ailanthus altissima (Mill.) Swingle), gymnocladus dioicus (Gymnocladus dioicus (L.) K.Koch), ash maple (Acer negundo L.). The pipette method was used to determine the granulometric composition of the park's soils. The results obtained indicate that the vast majority of soils are light loam by their granulometric composition, and the content of physical clay ranges from 20.60 to 28.59 %. At the same time, the soils under the common bitter chestnut (Aesculus hippocastanum L.), sugar maple (Acer saccharum Marshall) and ash maple (Acer negundo L.) are represented by medium loamy granulometric composition, where the content of physical clay ranges from 35.05 to 38.89 %. Among the predominant fractions in the studied soils, it should be noted the sand fraction (particle size 1–0.05 mm), the coarse dust fraction (particle size 0.05–0.01 mm) and the silt fraction (particle size <0.001 mm). This, in turn, led to the formation of the following types of particle size distribution: light sandy-dusty loam, light silty-dusty loam, light dusty-sandy loam, and medium silty-sandy loam. The predominance of these fractions ensures high water permeability of the soil, favorable thermal and air conditions. At the same time, the silt fraction plays a leading role in the formation of soil structure, and also provides high absorption capacity and coagulation ability. However, it is important to control the level of soil acidity, as it is the silt fraction that can lead to its increase. At the same time, light loamy soils retain moisture poorly, which in turn can lead to moisture deficits in the absence of sufficient rainfall. Particular attention should be paid to monitoring studies of the content of toxic substances in soils, as anthropogenic pollution can cause coarse dust to contain toxic substances, which can affect soil quality and its suitability for use. The study emphasizes the importance of studying the particle size distribution of soils under introduced trees for the proper management of park ecosystems. Particle size analysis provides valuable data on soil structure that affects soil permeability, water removal, and nutrient availability to plants. The ability to understand and predict changes in particle size distribution can be useful in ensuring the sustainable ecological sustainability of a park and optimizing conditions for the growth and development of introduced woody plants.
Features of the granulometric composition of soils under introduced deciduous and ornamental woody plants in Taras Shevchenko Park
Keywords: гранулометричний склад; particle size distribution; інтродукована рослинність; introduced vegetation; фракція піску; sand fraction; фракція мулу; silt fraction